(untitled) (Research, Society and Development, 2021)
Objective: to report the experience of nurses in patient care management in the service of gastric endoscopic methods. Method: this is an experience report of the professional experience of a group of nurses in the Gastric Endoscopic Methods Service, in a hospital in Rio de Janeiro, in March 2020-21. Results: the professional experience in the pandemic period allowed for reflection on the practice of nurses in the management of care actions, with direct actions involving the implementation of protocols, such as patient screening, and adjustments in others, such as post-procedure recovery; and in indirect actions, calculations on forecasting and provision of materials and equipment, changes in work flows, setting of signs and theoretical-practical reinforcements in disinfection and cleaning routines. Final considerations: the experience allowed the development of a critical and reflective look at managerial actions and biosafety measures, in the presence of a pandemic, favoring clinical reasoning and the improvement of direct and indirect actions contemplating the patient, family/companion, professionals and institution.